Effect of louvres on the thermal efficiency of panel radiators - Yedikardes, Yildiray; Teke, Ismail (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
In this study, two radiators on which louvres had been made up on either outer surface or inner surface, were experimentally contrasted within an experimental setup which heats water between an average temperature difference range of Delta T = 30 K to 60 K. Constructive details and dimensions of experimental test section's orientations having 6 different positions were given in detail in the paper. Positions include the situation of the panel radiator without louvre, louvres on front surface-single slice, louvres on back surface-single slice, louvres on back surface-single slice, and louvers on back surface-single slice with a chimney, louvres on back surface- 3 slices in a row. Detailed uncertainty analyses were given in order to calculate the uncertainties of water inlet and outlet temperatures, and heat output values. CFD analyses have been carried out to have air velocity and temperature distribution around the sample panel radiators after the validation with experiments. CFD results were found to be in good agreement with experiments having tolerable deviation varied from 10.73% to 24%. Almost all experimental findings including measured data points were declared in a Table for other researchers' usage for their validation issues. 8 number of empirical correlations have been proposed in order to determine the heat outputs regarding with the different configurations of the test section. Finally, effect of louver space on the heat outputs was also shown in the paper.
Keywords: Radiator; Natural convection on vertical slabs; Louvre; TUBE HEAT-EXCHANGERS; LOUVERED-FIN; FLAT TUBE; PERFORMANCE; PLATE; OPTIMIZATION; CONVECTION; Thermodynamics; Mechanics